Engineering Spin States of Isolated Copper Species in a Metal–Organic Framework Improves Urea Electrosynthesis - Gao, Yuhang; Wang, Jingnan; Yang, Yijun; Wang, Jian; Zhang, Chuang; Wang, Xi; Yao, Jiannian (Nano-micro letters, 2023)
Highlights The single-atom Cu species with S = 0 spin ground state in Cu III -HHTP have been fabricated. The Cu III -HHTP exhibits remarkable performance with a high urea yield of 7.780 mmol h −1 g −1 with the corresponding Faradaic efficiency of 23.09% at − 0.6 V (vs. RHE). Low spin state and empty ( d x 2 -y 2 0 ) orbitals are favorable to enhance the production urea of C–N coupling process. The catalytic activities are generally believed to be relevant to the electronic states of their active center, but understanding this relationship is usually difficult. Here, we design two types of catalysts for electrocatalytic urea via a coordination strategy in a metal–organic frameworks: Cu III -HHTP and Cu II -HHTP. Cu III -HHTP exhibits an improved urea production rate of 7.78 mmol h −1 g −1 and an enhanced Faradaic efficiency of 23.09% at − 0.6 V vs. reversible hydrogen electrode, in sharp contrast to Cu II -HHTP. Isolated Cu III species with S = 0 spin ground state are demonstrated as the active center in Cu III -HHTP, different from Cu II with S = 1/2 in Cu II -HHTP. We further demonstrate that isolated Cu III with an empty d x 2 -y 2 0 orbital in Cu III -HHTP experiences a single-electron migration path with a lower energy barrier in the C–N coupling process, while Cu II with a single-spin state ( d x 2 -y 2 1 ) in Cu II -HHTP undergoes a two-electron migration pathway.